Long-period gratings fabricated in photonic crystal fibre - Kalli, Kyriacos; Dobb, Helen L.; Petrovic, Jovana S. (My University, 2005)
Long period gratings in two types of photonic crystal fibre have been studied. The gratings display negligible temperature sensitivity but useful sensitivity to other measurands. Theoretical modelling suggests that unusual phase matching conditions apply
Keywords: Photonic crystals; Optical fibers; Diffraction gratings; Crystals